Complex cobalt silicates and germanates crystallizing in a porous three-dimensional framework structure. Issue 6 (23rd January 2020) - Usman, Mohammad; Smith, Mark D.; Kocevski, Vancho; Besmann, Theodore; zur Loye, Hans-Conrad
Abstract : Single crystals of new cesium cobalt silicates and germanates exhibiting three-dimensional, ion-exchangeable crystal structures were grown from a mixed CsCl–CsF flux, and their electronic and magnetic properties were studied using DFT calculations. Abstract : Four new cesium-containing cobalt oxide complexes were reported. Cs(Co0.5 Si0.5 )SiO4 (1 ), Cs1.29(5) Co0.69(5) Ge1.81(5) O5 (2 ), and its ordered analogue Cs2 CoGe4 O10 (3 ) were synthesized using a mixed CsCl–CsF flux at 850 °C or 900 °C. The structure of (1 ) closely resembles that of known zeolite and feldspar structures, and (1 ) crystallizes in the noncentrosymmetric monoclinic space group Im with lattice parameters of a = 8.9926(4) Å, b = 5.4599(2) Å, c = 9.3958(6) Å, and β = 91.5928(18)°. Complexes (2 ) and (3 ) crystallize in the same new structure with a highly porous three-dimensional framework in the tetragonal space group I 4̄ with lattice parameters of a = 7.4239(14) Å and c = 13.169(3) Å for (2 ) and a = 7.3540(6) Å and c = 13.1122(11) Å for (3 ). The formation of (2 ) vs. (3 ) can be controlled based on slight variations in the quantities of the starting materials. Single-crystal-to-single-crystal ion exchange of (1 ) in a molten RbNO3 bath resulted in 14% Cs exchange with Rb, affording the composition Cs0.86 Rb0.14 (Co0.5 Si0.5 )SiO4 (4 ). First-principles density functional theory calculations were performed to elucidate the electronic and magnetic properties and stabilities of (1 ) and (3 ) at 0 K.